Gender Representation in The Illustration of Indonesian 8th Grade EFL Textbook - Artini, Ni Nyoman; Padmadewi, Ni Nyoman; Suwastini, Ni Komang Arie; Rachman, Dzul; Saputra, I Nyoman Pasek Hadi (Universitas Pendidikan Ganesha, 2024)
Along with the growing awareness of gender equality, language learning should start working on issues of gender equality besides focusing on language acquisition. Using interactive qualitative methods from Miles, Huberman, and Saldana combined with Peirce's semiotics, this study aimed to examine the depiction of gender roles displayed in illustrations of English textbooks for eighth grade students. The results showed that there were attempts to deconstruct the gender roles of both men and women, although gender stereotypes remained common. The emerging stereotypes were depictions of men with darker skin colour and male characters doing outdoor activities. In addition, the proportion of female characters appeared less frequent than male characters. Meanwhile, the deconstruction raised was the role of boys in household activities such as cooking, sweeping, wrapping gifts, setting up dining table, and using clothes in pastels while the female characters were depicted in outdoor activities. However, the delivered deconstruction was subtle as identified in female characters engaged in outdoor activities tended to get safer settings than male characters. Considering that children’s perception on gender are affected by language, it is important for parties involved in language learning to be aware of things that may extend gender role disparities found in the widely accessed learning material such as textbooks and address these issues while conducting their language instruction.